Performance evaluations of digital watermarking system - Yusof, Yusnita; Khalifa, Othman Omran (IIUM Press, 2011)
A properly designed and implemented watermarking system needs to be evaluated of its performance so that it can be compared with other systems designed for the same purpose using the same conditional/experimental parameters. Muharemagic and Furht (2003) stated that by definition, watermarking is a technique for embedding a watermark into a cover image imperceptibly and robustly. Therefore a quality of a new or improved watermarking system can be measured by evaluating these two properties